Pomegranate juice anthocyanidins induce cell death in human cancer cells by mobilizing intracellular copper ions and producing reactive oxygen species - Farhan, Mohd; Rizvi, Asim; Ali, Ferasat; Ahmad, Aamir; Aatif, Mohammad; Malik, Arshi; Alam, Mir Waqas; Muteeb, Ghazala; Ahmad, Saheem; Noor, Awal; Siddiqui, Farhan Asif (Frontiers in Oncology, 2022)
Anthocyanidins are the most abundant polyphenols in pomegranate juice. This class of molecules includes Delphinidin (Del), Cyanidin (Cya), and Pelargonidin (Pel). Using prostate, breast and pancreatic cancer cell lines PC3, MDA-MB-231, BxPC-3 and MiaPaCa-2, we show that anthocyanidins inhibit cell proliferation (measured by MTT assay) and induce apoptosis like cell death (measured by DNA/Histone ELISA). Copper chelator neocuproine and reactive oxygen species scavengers (thiourea for hydroxyl radical and superoxide dismutase for superoxide anion) significantly inhibit this reaction thus demonstrating that intracellular copper reacts with anthocyanidins in cancer cells to cause DNA damage via ROS generation. We further show that copper-supplemented media sensitizes normal breast epithelial cells (MCF-10A) to Del-mediated growth inhibition as determined by decreased cell proliferation. Copper supplementation results in increased expression of copper transporters Ctr1 and ATP7A in MCF-10A cells, which is attenuated by the addition of Del in the medium. We propose that the copper mediated, ROS-induced mechanism of selective cell death of cancer cells may in part explain the anticancer effects of anthocyanidins.